2022
DOI: 10.1192/bjo.2022.66
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the identification and management of mental health and domestic abuse among pregnant women during the COVID-19 lockdown: regression discontinuity study

Abstract: Background Domestic violence and abuse (DVA) and mental illness during pregnancy have long-lasting and potentially serious consequences, which may have been exacerbated during the COVID-19 pandemic. Aims To investigate how the UK COVID-19 lockdown policy influenced the identification of DVA and depressive symptoms during pregnancy in health services in South-East London in Spring 2020, using eLIXIR (Early-Life Data Cross-Linkage in Research) maternity and mental routine healthcare data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 47 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…The issues surrounding the implementation of hospital and governmental guidelines was raised in twenty-two studies (1, 4, 12, 23, 24, 26, 29, 32, 34, 3740, 44, 45, 53, 55, 6265). Policies were everchanging and not well communicated by hospitals, causing confusion and uncertainty; birth plans were altered to satisfy these new regulations (4).…”
Section: Resultsmentioning
confidence: 99%
“…The issues surrounding the implementation of hospital and governmental guidelines was raised in twenty-two studies (1, 4, 12, 23, 24, 26, 29, 32, 34, 3740, 44, 45, 53, 55, 6265). Policies were everchanging and not well communicated by hospitals, causing confusion and uncertainty; birth plans were altered to satisfy these new regulations (4).…”
Section: Resultsmentioning
confidence: 99%
“…A large study was also conducted that utilised linked maternity and mental health records held within the Early Life Cross-Linkage in Research (eLIXIR) database ( 34 ). Data from three NHS Foundation Trusts (including one Mental Health Trust) in South London constitute the eLIXIR database ( 34 , 35 ). Research using an interrupted time series study design found that the rate of recording domestic abuse and violence during national lockdown restrictions was reduced by 78% in mental healthcare settings.…”
Section: Available Evidencementioning
confidence: 99%
“…However, a UK data linkage study of 26 447 pregnant women's clinical records between October 2018 and August 2020 found that identification of DVA by secondary mental health services reduced by 78%, remaining low even after restrictions were lifted 57 . In maternal care services, the proportion of women screening positive for depressive symptoms increased by 40% and returned to baseline after restrictions ceased.…”
Section: Mental Health Impactsmentioning
confidence: 99%